The most-liked and least-liked television personalities as perceived by selected students of the University of the Philippines High School - Pornnimitra, Sununtar 1945- (1974)
The perceptions of selected high school students regarding their most-liked and least-liked personalities on television were determined in this study.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Television broadcasting -- Philippines; Television audiences